2015
DOI: 10.1002/2014wr016152
|View full text |Cite
|
Sign up to set email alerts
|

Valuing recreational fishing quality at rivers and streams

Abstract: This paper describes an economic model that links the demand for recreational stream fishing to fish biomass. Useful measures of fishing quality are often difficult to obtain. In the past, economists have linked the demand for fishing sites to species presence-absence indicators or average self-reported catch rates. The demand model presented here takes advantage of a unique data set of statewide biomass estimates for several popular game fish species in Michigan, including trout, bass and walleye. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 44 publications
1
30
1
Order By: Relevance
“…Although biomass may be an imperfect measure of the availability of catchable fish to anglers, measures of catchable fish were not available for modeling. Furthermore, high biomass values in the Michigan Rivers Inventory data set were generally driven by the presence of large fish in a given sample (T. Zorn, Michigan Department of Natural Resources, personal communication), and a companion MAPPING OF MICHIGAN GAME FISH BIOMASS 303 paper (Melstrom et al 2015) demonstrated that fish biomass predictions across the landscape as generated by the current study were significantly correlated with angler choices about where to fish.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Although biomass may be an imperfect measure of the availability of catchable fish to anglers, measures of catchable fish were not available for modeling. Furthermore, high biomass values in the Michigan Rivers Inventory data set were generally driven by the presence of large fish in a given sample (T. Zorn, Michigan Department of Natural Resources, personal communication), and a companion MAPPING OF MICHIGAN GAME FISH BIOMASS 303 paper (Melstrom et al 2015) demonstrated that fish biomass predictions across the landscape as generated by the current study were significantly correlated with angler choices about where to fish.…”
mentioning
confidence: 73%
“…Until our fish standing crop estimates are connected to beneficiaries, we cannot draw detailed conclusions about the benefit or value of this ecosystem service to society. Thus, the essential next step for this research is to quantify angler behaviors relative to fish biomass availability and to assign values to biomass in the rivers where it is produced (see companion paper by Melstrom et al 2015). With biophysical and economic information in hand, sport fishery managers should be able to utilize new spatial knowledge to improve fisheries management to the benefit of anglers.…”
Section: Discussionmentioning
confidence: 99%
“…Brook trout is a highly valued and sought fisheries resource throughout its range (Melstrom, Lupi, Esselman, & Stevenson, ; Power, ; Scott & Crossman, ). The species is endemic to northeastern North America ranging from the Hudson Bay in Manitoba to Newfoundland and Labrador, and southerly throughout the Appalachian Mountains to Georgia in the United States (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Agnarsson et al (2008); Lawrence (2005); Lew and Larson (2012); Raguragavan et al (2013); Hutt et al (2013); Yamazaki et al (2013); Melstrom et al (2015)). Studies estimating national level expenditures include Toivonen et al (2004), which reports angler expenditures in ve Scandinavian countries, including Iceland, ranging from US$ 23281 million per annum.…”
Section: Introductionmentioning
confidence: 99%